THE DEVELOPMENT OF GOVERNMENT POLICY ON TECHNICAL EDUCATION IN NIGERIA, 1960-1980 (1986)
Chapter three delves into the moves made by the Nigerian Government to evolve a plan for action in the provision of technical education having now fully realised the shortcomings of the policy it had pursued up till the time of independence in 1960. The fourth chapter examines the policy pursued by the government on technical education between 1970 and 1980 in order to meet the manpower needs of Nigeria foreshadowed by Ashby. For the first time, a National Policy on education was produced by the government as a means of giving direction to educational development in the country. In the next two chapters, an attempt is made to review and evaluate the practice of the policy maintained by the government by considering its implementation measures of the points highlighted in the policy statements enunciated during the period under study. The concluding chapter summarizes the government's achievements and shortcomings in putting into practice its formulated policies on technical education.